PENGARUH BRAND REPUTATION TERHADAP INTENTION TO APPLY DENGAN CREDIBILITY ON SOCIAL MEDIA SEBAGAI VARIABEL MEDIASI - Irawan, Leony Jaslin; Rante Tasak, Ferdianty Rosalynda; Horas, Lavenia; Maichal, Maichal (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025DO - 10.24843/EEB.2025.v14.i03.p02, 2025)
This study aims to understand the influence of brand reputation on prospective students' intention to apply to higher education institutions, considering the mediating role of information credibility obtained through social media. In recent years, STIE Ciputra Makassar has experienced fluctuations in student enrollment interest, despite being part of the Ciputra Group, which has a strong reputation in entrepreneurship education. Challenges in attracting prospective students may stem from public perceptions of the institution's reputation and how information about it is conveyed and received. This study adopts a quantitative approach, employing statistical methods to analyze data collected through questionnaires from 133 first-year students of the 2024 cohort. Data analysis was conducted using SmartPLS 4 to identify relationship patterns between variables. The results indicate that brand reputation has a positive and significant influence on information credibility in social media, and information credibility in social media positively and significantly affects the intention to apply. Thus, brand reputation impacts the intention to apply, with information credibility on social media acting as a mediator. These findings highlight a strong relationship between these factors, reinforcing that brand reputation influences the intention to apply through the mediation of social media credibility.